Validation and efficacy of a tele-yoga intervention for improving psychological stress, mental health and sleep difficulties of stressed adults diagnosed with long COVID: a prospective, multi-center, open-label single-arm study - Bhargav, Hemant; Raghavan, Vijaya; Rao, Naren P.; Gulati, Kankan; Binumon, Kodikuthiyel Vijayan; Anu, K. N.; Ravi, Sridhar; Jasti, Nishitha; Holla, Bharath; Varambally, Shivarama; Ramachandran, Padmavati (Frontiers in Psychology, 2024)
The objective of this study was to validate and test the efficacy of a 16-week tele-yoga intervention for perceived stress, anxiety, depression, and insomnia in individuals who had had COVID-19 infection in the previous year, and had reported moderately high levels of psychological stress (PSS 14). 25-minute and 50-minute versions of the program were developed. They were then validated using Lawshe's content validity ratio after obtaining feedback from 20 yoga therapy experts. The safety and efficacy of the two programs were subsequently tested in a prospective, multicenter, open-label single-arm study. Eighty-six adults (18 male, 68 female) were recruited from two tertiary mental healthcare institutions, 48 in NIMHANS, Bengaluru; and 38 in SCARF, Chennai. Participants were assessed at weeks zero, 4, and 16 using validated tools. Data were analyzed using a Mixed Model, Intention to Treat approach. After week 16, 31 subjects remained in the trial and continued to practice yoga without any side effects.Results at week 4 included significant reductions in levels of perceived stress, anxiety, and insomnia, but not depression; improvements were maintained at week 16. Correlations between number of yoga sessions and post-intervention PSS scores were negative (r = -0.49), and significant. Both tele-yoga programs proved safe, useful tools to counteract perceived stress, anxiety and insomnia. Future trials should explore the utility of tele-yoga as a tool to enhance wellbeing and manage stress.